Research on employment for persons with severe mental illness - Fisher, William H. (Elsevier JAI, 2004)
Over the centuries work for persons with severe mental illness has ranged from virtual slave labor to institutional peonage to contemporary rehabilitative programs that seek to assist individuals in re-entering the workplace. How best to do this remains an open question however, and has captured the attention of researchers from a broad range of disciplines, from rehabilitation research to labor economics. This volume provides a sense of this diversity and an overview of research perspectives in this critically important area. Included are chapters discussing important new theoretical frameworks, issues in the evaluation of programmatic efforts to enhance employment opportunities, and discussions grounded in large scale social and economic perspectives.
Keywords: Mentally ill -- Employment.; Mentally ill -- Rehabilitation.; Care of the mentally ill.; Political Science -- Labor & Industrial Relations.; Social Science -- People with Disabilities.; elektronické knihy; electronic books